Developing Literacy Wheel Media: An Innovation to Improve English Reading Skills of Primary Learners - Oktadela, Resy; Elida, Yusti; Roziah, Roziah; Ismail, Syofianis (Universitas Pendidikan Mandalika, 2025)
The Literacy Wheel stands out as a promising tool designed specifically to enhance English language skills. This media not only makes the learning process more engaging but also addresses key linguistic competencies. The Literacy Wheel significantly boosts students’ interest in learning English. Therefore, efforts are needed to assist students in learning English by creating an interactive learning medium called the Literacy Wheel (Rossi) to enhance students' learning motivation. The focus of this study is to analyze the validity and practicality of the developed learning media. The subjects of the study were third-grade students. The method used was Research and Development, employing the ADDIE model. The data used in the study included a preliminary study with interview techniques, validation by subject matter and media experts, and questionnaires to gather teacher and student responses to the learning media. The results showed that 98% of the Literacy Wheel media aligned with the material, and 95% of it was deemed valid for use in learning. The product received positive responses from students, with 79, 30% of them expressing enjoyment of the Literacy Wheel media. Based on these findings, the authors suggest that the content in the Literacy Wheel media be expanded to include more diverse subjects.